2014
DOI: 10.4140/tcp.n.2014.823
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron: A Beta-3 Agonist for Overactive Bladder

Abstract: Objective To review the literature regarding the efficacy and safety of mirabegron for the treatment of overactive bladder (OAB). Data Sources A literature search was performed using MEDLINE (PubMed) prior to 12/31/2013 using the terms “mirabegron” and “randomized-controlled trial.” Study Selection/Data Extraction All published, double-blind, randomized controlled trials assessing mirabegron were included. Articles were reviewed and included if mirabegron was used as monotherapy and if the primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…37 As part of a newer class of agents, mirabegron stimulates β-3 adrenergic receptors to relax bladder smooth muscle and achieve the same effect as the anticholinergics. 38 These medications can increase PVR urine volume, so patients should be monitored for the development of retention and need to perform CIC.…”
Section: Failure To Storementioning
confidence: 99%
“…37 As part of a newer class of agents, mirabegron stimulates β-3 adrenergic receptors to relax bladder smooth muscle and achieve the same effect as the anticholinergics. 38 These medications can increase PVR urine volume, so patients should be monitored for the development of retention and need to perform CIC.…”
Section: Failure To Storementioning
confidence: 99%
“…8,9 Similarly, adrenergic receptors are also located throughout the body with resultant side effects, especially important being cardiovascular effects. 10 While more targeted than the systemic approach with potentially fewer side effects, OnabotulinumtoxinA injections provide a minimally invasive treatment that needs to be repeated to maintain clinical efficacy. 11 While potentially more durable, the MIS procedure involves an invasive surgery with more tissue disruption, longer recovery time, and potential for interprocedural variations.…”
Section: Introductionmentioning
confidence: 99%
“…Mirabegron targets the β3‐adrenoceptor, causing direct relaxation of the detrusor muscle, inhibition of spontaneous contractile activity in the bladder, and reduction in bladder afferent activity 20 . ‐ 22 Pooled analysis of published studies showed that mirabegron 50 mg was associated with a reduction in mean micturition per 24 hours and incontinence episodes per 24 hours 21 . Mirabegron is well tolerated, with negligible dry mouth; however, there is an increase in cardiovascular events (most commonly hypertension) associated with its use 20 .…”
Section: Stepwise Approach To Treatment Optionsmentioning
confidence: 99%